Interactive foresight on the Hungarian SMEs. Issue 4 (5th August 2014) - Hideg, Eva; Nováky, Erzsébet; Alács, Péter
Abstract : Purpose: – The aim of this study is to present a concept of interactive foresight process, its theoretical and methodological considerations and a foresight exercise concerning the development of knowledge economy in the Central Hungarian Region. Design/methodology/approach: – A methodology of interactive foresight process for creating regional future concepts is developed, which is based on a specific meaning of integral futures and uses online solutions, too. Findings: – Personal meetings with small and medium enterprise (SME) stakeholders and the works of interactive communications with feedbacks within and among stakeholder groups was organized around the research homepage. The networking created the interconnection and the feedbacks between the stakeholders and the futurist group in the process of shaping regional future ideas. The online networking is running. Research limitations/implications: – The low number of stakeholders can limit the validity and acceptance of futures ideas created by this process. Practical implications: – The developed interactive foresight process can also be applicable at different organizational levels and in different fields for shaping shared future ideas. Social implications: – Application of interactive foresight process can contribute to the development of anticipatory democracy. Originality/value: – A theoretically based interactive foresight process has been developed in which stakeholders can participate not only interactively in the foresight process but they can implement the achievements in their enterprising activity as well. The participants were interested in foresight and cooperative during the whole process because they learned the use of foresight tools through collective solution of practical tasks which were important for them.